2005
DOI: 10.1071/ar04185
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of sugarcane to mycorrhizal spore density and phosphorus rate

Abstract: Abstract. Arbuscular mycorrhizal (AM) fungi, commonly found in long-term cane-growing fields in northern Queensland, are linked with both negative and positive growth responses by sugarcane (Saccharum spp.), depending on P supply. A glasshouse trial was established to examine whether AM density might also have an important influence on these growth responses. Mycorrhizal spores (Glomus clarum), isolated from a long-term cane block in northern Queensland, were introduced into a pasteurised low-P cane soil at 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…However, adding P does not always elicit a strong growth response in sugarcane (Kelly et al, 2001(Kelly et al, , 2005. The enriched soil nutrient content in the high compost treatment was also evident from the substantially greater production of first-season water (164) (8) (84) sprouts than in other treatments.…”
Section: Discussionmentioning
confidence: 71%
“…However, adding P does not always elicit a strong growth response in sugarcane (Kelly et al, 2001(Kelly et al, , 2005. The enriched soil nutrient content in the high compost treatment was also evident from the substantially greater production of first-season water (164) (8) (84) sprouts than in other treatments.…”
Section: Discussionmentioning
confidence: 71%
“…ZANGARO et al (2000) found that trees in later forest succession stages are less dependent than pioneer tree species in initial phases of succession, meaning that forest in climax are not responsive to AMF root colonization. Similarly, KELLY et al (2005) studying growth responses of sugarcane to different mycorrhizal spore density concluded that sugarcane is poorly responsive to AMF, although it is unlikely that longterm sugarcane fi elds suffer a yield reduction because of mycorrhizal root colonization.…”
Section: Resultsmentioning
confidence: 99%
“…Arbuscular mycorrhizae including Glomus spp. have also been found in the roots and rhizosphere of field-grown sugarcane plants, although no clear contribution to plant nutrition has been demonstrated (Kelly et al 2005).…”
Section: The Rootmentioning
confidence: 99%